DETERMINATION OF VIBRATION RESISTANCE OF AUTOMOBILE BRICKS - Khaydarali Fayzullayev (American Journals Publishing, 2023)
The purpose of his work is to study "Analysis of vibrations in fixed joints of vehicles". Studying vibrations in various parts of cars and developing scientifically based recommendations as a result of research. Road transport is an integral part of the country's transport system. The efficiency of many sectors of the economy depends on transport costs.
Keywords: Car, cargo, gas cylinder, transport, movement, energy, engine, power, aggregates.